Specific Features of Teaching Handball Sports to Senior Students in Secondary Schools - F.A.Tashpulatov (Zien Journals, 2022)
The article talks about the features of teaching the type of handball sort to uppergraders, the role of the handball sport in educating the spiritual and volitional characteristics of schoolchildren, developing their physical qualities
Keywords: hand ball; strength; dexterity; agility